2004
DOI: 10.1200/jco.2004.12.015
|View full text |Cite|
|
Sign up to set email alerts
|

Thin Primary Cutaneous Malignant Melanoma: A Prognostic Tree for 10-Year Metastasis Is More Accurate Than American Joint Committee on Cancer Staging

Abstract: Growth phase, mitotic rate, and sex are important prognostic factors for patients with thin melanomas, and they identify subgroups at substantial risk for metastasis. After validation in other populations, the proposed prognostic tree will be useful in the design of clinical trials and clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
162
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(180 citation statements)
references
References 32 publications
13
162
0
2
Order By: Relevance
“…High-grade atypical melanocytic nevi revealed the features of established neoplasms (advantageous kinetics, expressed telomerase, and accumulated microsatellite abnormalities, Figure 4), 1 but different from both radial-and vertical-growthphase malignant melanoma. 41,42 The microsatellite patterns do not fit a continuous evolution model from high-grade dysplasia to vertical-growth-phase melanoma: The profiles of malignant melanomas in radial and vertical growth phases (phenotype, kinetics, and CCR microsatellite profile) were different, in that radial-growth-phase malignant melanomas showed microsatellite patterns not fitting the transition between high-grade atypical melanocytic nevi and vertical-growth-phase malignant melanomas. This profile unlikely represents a continuous evolution within a common pathway (linear model of progression); this will explain the difficulty in designing common screening or therapeutic targets for these two different malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…High-grade atypical melanocytic nevi revealed the features of established neoplasms (advantageous kinetics, expressed telomerase, and accumulated microsatellite abnormalities, Figure 4), 1 but different from both radial-and vertical-growthphase malignant melanoma. 41,42 The microsatellite patterns do not fit a continuous evolution model from high-grade dysplasia to vertical-growth-phase melanoma: The profiles of malignant melanomas in radial and vertical growth phases (phenotype, kinetics, and CCR microsatellite profile) were different, in that radial-growth-phase malignant melanomas showed microsatellite patterns not fitting the transition between high-grade atypical melanocytic nevi and vertical-growth-phase malignant melanomas. This profile unlikely represents a continuous evolution within a common pathway (linear model of progression); this will explain the difficulty in designing common screening or therapeutic targets for these two different malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…62 The Philadelphia group has shown a 10-year metastatic rate in men with vertical growth phase melanoma of 31% when a mitotic rate of greater than 0 was identified, vs a 4% mortality rate when the mitotic rate was 0. 63 Barnhill et al 58 studied the impact of mitotic rate upon survival for 650 consecutive primary cutaneous melanoma patients in a logistic regression model. Using 0 vs 1-6 vs 46 mitoses per square millimeter as their discriminative categories, they found that both moderate (1-6/ mm 2 ) and high (46/mm 2 ) mitotic activity were independent prognostic variables.…”
Section: Mitotic Ratementioning
confidence: 99%
“…The protocol was approved by Institutional Review Board at University of Pennsylvania. One hundred and forty patients were selected from a total of 489 patients who had at least 10 years of follow-up and had paraffin blocks available for IHC staining [9]. Subjects were selected using stratified random sampling where strata were defined by the occurrence of a ten-year metastasis and tumor thickness (three groups were defined using AJCC T1-T3 criteria as: < 1mm, 1-2 mm and > 2 mm).…”
Section: Methods Study Patients and Study Designmentioning
confidence: 99%